Synthesizing Middle Grades Research on Cultural Responsiveness: The Importance of a Shared Conceptual Framework - Brianna L. Kennedy; Kathleen Brinegar; Ellis Hurd; Lisa Harrison (Middle Grades Review, 2016)
In conducting a literature review of 133 articles on cultural responsiveness in middle level education, we identified a lack of shared definitions, theoretical frameworks, methodological approaches, and foci, which made it impossible to synthesize across articles. Using a conceptual framework that required: 1) clear definitions of terms; 2) a critically conscious stance; and 3) inclusion of the middle school concept, we identified 14 articles that met these criteria. We then mapped differences and convergences across these studies, which allowed us to identify the conceptual gaps that the field must address in order to have common definitions and understandings that enable synthesis across studies.